Key Pathways to High-Speed Internet in the Middle East and North Africa : Spurring Competition and Building New Networks - Gelvanovska, Natalija; Rogy, Michel; Rossotto, Carlo Maria (World Bank Group, Washington, DC, 2015)
Most countries of the Middle East and North Africa (MENA) region are falling behind in their quest to develop high-speed Internet for rapid socioeconomic development. Despite young adults’ rising use of social networking tools and solid progress in a few countries, most of the region’s Internet remains hobbled by monopolized, inadequate infrastructure; weak investment incentives; and high costs. High-speed (broadband) Internet can drive economic and social transformations. To realize that potential, a recent World Bank study finds that MENA countries must pursue a three-pronged approach: reduce costs by fully liberalizing access to the existing Internet infrastructure; support the resulting competition with independent national regulators working within a harmonized regional framework of regulation; and promote investments in new fiber-optic networks and other ultrafast broadband infrastructure (including Long-Term Evolution or LTE) alongside existing technologies. With these measures, plus aggressive strategies for sharing public works infrastructure and subsidies for rural access, MENA can leapfrog its current information and communication bottlenecks.